Towards Software Asset Management in Proprietary Software Ecosystems: A Participative Case Study - Costa, Luiz Alexandre; Outão, Juliana Carvalho; Simões, Jefferson Elbert; Santos, Rodrigo Pereira dos (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2024: Anais do XXIII Simpósio Brasileiro de Qualidade de Software, 2024)
The business landscape has evolved from isolated units to complex networks of interdependencies, leading to the rise of software ecosystems (SECO) with interconnected networks and strategic alliances around common technological platforms. Proprietary SECO (PSECO) involves private software artifacts managed by a central organization (keystone), which must establish governance policies, such as software asset management (SAM) practices, to maintain platform stability amid business evolution. This work investigated SAM practices within a large international organization through a participative case study as research method. We performed an exploratory study using network analysis techniques, revealing a scenario of greater dependency on an IT software provider. Next, we performed a qualitative study through semi-structured interviews to understand the practices employed by IT managers during SAM. Based on the results, we derived a process that combines network analysis tools and a value-complexity matrix to aid organizations in moving forward to robust SAM by finding attention points and defining practices aligned to the organization’s priorities.